TREE SPECIES DIVERSITY IN THE LOWLAND FOREST OF THE CORE ZONE OF THE BUKIT DUABELAS NATIONAL PARK, JAMBI, INDONESIA - RAHMAH RAHMAH; KUSWATA KARTAWINATA; NISYAWATI NISYAWATI; WISNU WARDHANA; ERWIN NURDIN (Reinwardtia, 2016)
RAHMAH, KARTAWINATA, K., NISYAWATI, WARDHANA, W. & NURDIN, E. 2016. Tree species diversity in the lowland forest of the core zone of the Bukit Duabelas National Park, Jambi, Indonesia. Reinwardtia 15(1): 11 - 26. — An analysis of the composition and structure of a one-hectare plot of forest on a lowland hill slope in the eastern core zone of the Bukit Duabelas National Park, Jambi, was conducted in October and November 2012. The objective of the study was to obtain a descriptive account of the structure and tree species composition of a lowland forest in the eastern core zone of the park. The plot was divided into 100 subplots of (10 m × 10 m) each and the seedling subplots (5 m × 5 m) were nested in the sapling subplots. A total of 414 trees were recorded with DBH (Diameter at Breast Height) ?10 cm, representing 113 species and 38 families, with the total BA (Basal Area) of 25.71 m2 and Shannon- Wiener diversity index of 4.29. Prunus arborea with IV (Importance Value) of 19.19 is the dominant species and the other prevalent species were, Dracontomelon dao (IV =11.46) and Hydnocarpus sp. (IV =11.38). A total of 44 species (38.9%) had each density of 1 tree/ha, which may be considered locally rare. Ficus fistulosa had the highest density (24 trees/ha) and Prunus arborea had the highest BA (3.28 m2 = 12.8% of the total). Only 10 species had F (frequency) of 8-18%, of which Hydnocarpus sp. had the highest (18%); the remaining species had F